Pendidikan Dan Peran Serta Masyarakat - Andini Sukma Suci; Royriah Hasibuan; Agus Triatma; Muhammad Zulham Munthe (Insan Zenius Ilmiah, 2024)
Education is a process that focuses on developing and changing students' behavior through transmitting knowledge, attitudes, beliefs, skills, and other aspects of behavior. Education is considered an important component in achieving social goals and national development. This study examines the relationship between education and society and the role of both in creating a quality generation. The background of this study emphasizes the importance of education in developing children's insight into ideology, politics, religion, society, culture, and defense and security. Education aims to bring progress to individuals, society, and the state to achieve national development. This study also identifies several problem formulations, namely the definition of education and society, the function and role of education for society, and therelationship between education and society to achieve quality learning goals. This study aims to understand education and society, identify the functions and roles of education for society, and explore the relationship between education and society to achieve quality learning goals. This study confirms that education plays a vital role in individuals' socialization and preservingcommunity culture. The functions of education include social control, cultural preservation, workforce development, and social change. This study alsodiscusses the importance of collaboration between schools, families, and communities in improving the quality of education. Effective curriculum implementation and the community's active role in supporting education are the keys to achieving national development goals and creating a future generation that is knowledgeable, technological, and faithful. Thus, education is an agent of social change that contributes significantly to developing individuals and communities, ensuring the achievement of national goals through a quality and sustainable learning process.